On-farm demonstration, testing and dissemination of boiling water treatment for plantain (Musa spp.) sucker sanitation in Southern Cameroon - Hauser, A.; Amougou, D.; Bengono, B.; Ngo Kanga, F.; Pekeleke, M. (International Society for Horticultural Science, 2010)
Plantain (*Musa* spp.) is an important staple food and cash crop in West and Central Africa. It is highly susceptible to a complex of root and corm pests and diseases and yields are low. Farmers practice virtually no pest or disease control. A simple inexpensive method to clean suckers of most pests and diseases is submerging suckers in boiling water for 30 s. However, with no extension system in place and farmers dispersed in forested territory with poor road infrastructure, disseminating the technology poses a difficulty. Unlike distributing new germplasm, new technologies need to be taught to farmers, their positive effects need to be demonstrated and farmers may have to accept behavioral changes in order to adopt. In the current case, there is the additional need to convince farmers of the need for a radical treatment to be administered to a commodity in short supply. The approach was a combination of workshop and hands-on demonstration plot establishments. Once farmers agreed to participate, technicians visited the village, gave lessons on plantain sucker health, the presence, symptoms and consequences of nematode (*Radopholus similis*) infestation, the concept of transmission of pests and diseases and the principle of heat treatment. Farmers prepared suckers for treatment. Treated and untreated suckers were planted in adjacent plots. After the initial workshop phase, adoption ranged from 32--47% (mean 39%). Follow up revealed that many demonstration plots had been expanded, or abandoned in favor of larger fields planted to 'boiling water treated' suckers. Negative consequences of introducing the 'boiling water treatment' included social conflict between workshop participants and non-participants and farmers using the technique versus those continuing to plant traditionally prepared suckers. The major reason for abandoning demonstration plots or advanced trials was a shortage of labor.